Pengaruh Tingkat Suku Bunga, Inflasi Dan Nilai Kurs Terhadap Harga Saham Perusahaan Perhotelan Yang Terdaftar Di Bursa Efek Indonesia Per Triwulannya Periode 2016-2018 - Rahmat Dewa Bagas Nugraha; H.M Nursito (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine and analyze the factors that affect stock prices through appropriate ratio analysis. As for the ratio of interest rates, inflation and exchange rates. Researchers want to know and analyze the effect partially or simultaneously between interest rates, inflation, and exchange rates on stock prices. This research is a quantitative study using secondary data. The object of this research is hotel companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sample used in this study were 3 hotel with certain characteristics. The results of research simultaneously using the F test show that there is no influence between interest rates, inflation and exchange rates on stock prices because the calculated value is smaller than the table. Partially with the t test it can be concluded that there is no influence between interest rates on stock prices because the tcount value in the interest rate variable is smaller than the t table. Likewise, the t calculation of inflation and the exchange rate is smaller than the t table, so that there is no partial effect of the two variables on stock prices. Keywords: Stock Prices, Interest Rates, Inflation and Exchange Rates